2001
DOI: 10.1211/0022357011776513
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of psychotropic drugs with monoamine oxidase in rat brain

Abstract: Literature observations indicate that some psychotropic drugs may have inhibitory activity towards monoamine oxidase (MAO). This study was undertaken to assess the potency, isozyme selectivity and mechanism of inhibition of representative first- and second-generation antidepressant drugs towards rat brain MAO-A and MAO-B. Five tricyclic antidepressants (imipramine, trimipramine, clomipramine, amitriptyline and doxepine) and three selective serotonin reuptake inhibitors (fluoxetine, fluvoxamine and citalopram) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Competitive inhibition of MAO-A and noncompetitive inhibition of MAO-B was found for these drugs. Similar results were obtained when different tricyclic antidepressants and SSRIs were examined with isolated rat brain mitochondria [198]. Fluoxetine and norfluoxetine showed affinities both for MAO-A [199] and MAO-B [200].…”
Section: Inhibition Of Maosupporting
confidence: 79%
“…Competitive inhibition of MAO-A and noncompetitive inhibition of MAO-B was found for these drugs. Similar results were obtained when different tricyclic antidepressants and SSRIs were examined with isolated rat brain mitochondria [198]. Fluoxetine and norfluoxetine showed affinities both for MAO-A [199] and MAO-B [200].…”
Section: Inhibition Of Maosupporting
confidence: 79%
“…Though a number of chemical compounds have been demonstrated as potent inhibitors of MAO activity in invertebrate tissues (Pan et al, 2000; Lee et al, 2001; Gnerre et al, 2001), there have not been many studies on mono amine oxidase activity under Pb‐intoxication. In the present study, a decrease in MAO activity was significant in mitochondria of cerebral cortex, hippocampus and cerebellum of 1% Pb‐treated rats, whereas a marginal increase in MAO activity was observed in 0.2% Pb‐treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…190−193 The three SSRIs fluoxetine, fluvoxamine, and citalopram, for instance, demonstrated a competitive inhibitory activity toward rat brain MAO in the micromolar range. 190 In an in vitro study with Xenopus laevis oocytes expressing cloned rat 5-HT 2C receptors, Ni and Miledi 191 observed that micromolar concentrations of fluoxetine blocked the responses of these receptor previously elicited by 5-HT. Using the same model system, fluoxetine was also shown to block both muscle and neuronal nicotinic acetycholine receptors (nAChR) in a noncompetitive and voltagedependent manner.…”
Section: Past and Current Efforts To Detect Ecotoxicological Effects mentioning
confidence: 99%